2019
DOI: 10.3390/molecules24132460
|View full text |Cite
|
Sign up to set email alerts
|

Metamaterial Lensing Devices

Abstract: In recent years, the development of metamaterials and metasurfaces has drawn great attention, enabling many important practical applications. Focusing and lensing components are of extreme importance because of their significant potential practical applications in biological imaging, display, and nanolithography fabrication. Metafocusing devices using ultrathin structures (also known as metasurfaces) with superlensing performance are key building blocks for developing integrated optical components with ultrasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 142 publications
(155 reference statements)
0
12
0
Order By: Relevance
“…Metamaterial (MTM), as an artificial medium, has several unusual features, such as negative (refractive index, permeability, and permittivity), making it appropriate for a variety of applications, including absorber 18 , bio sensing 19 , microwave imaging 20 , antennas 21 , metamaterial coding 22 , metamaterial lensing 23 , terahertz metamaterial 24 , and microwave devices like GPS5, WiMAX 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterial (MTM), as an artificial medium, has several unusual features, such as negative (refractive index, permeability, and permittivity), making it appropriate for a variety of applications, including absorber 18 , bio sensing 19 , microwave imaging 20 , antennas 21 , metamaterial coding 22 , metamaterial lensing 23 , terahertz metamaterial 24 , and microwave devices like GPS5, WiMAX 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterial, which consists of either negative permeability or negative permittivity can be classified as a single negative (SNG) metamaterial (Srinivasan et al 2019). The spread of metamaterial research, which revealed the MTMs unique characteristics such as negative permittivity (ε), negative permeability (µ) and negative refractive index (n), has led to a wide range of applications in microwave and optical regime such as reconfigurable antenna (Zhang et al 2019), satellite (Mao et al 2017), invisibility cloaking (Jing et al 2020), filters (Ahamed et al 2020) and superlenses (Lv et al 2019) etc. MTMs have recently originated with utilization in various frequency bands, as every frequency band has a diverse range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…The performance metamaterials are widely used in various fields due to their unique electromagnetic properties, such as metamaterial lenses [ 1 , 2 , 3 ], invisibility cloaks [ 4 , 5 ], surface sensors [ 6 , 7 , 8 , 9 ], wave absorbers [ 10 , 11 , 12 , 13 , 14 , 15 ], energy harvesters [ 16 ], etc. It is especially noteworthy that the energy crisis has brought new challenges and opportunities to all countries around the world [ 17 , 18 ], and solar energy has quickly won the favor of researchers because of its unique advantages.…”
Section: Introductionmentioning
confidence: 99%